Indoor Levels of Volatile Organic Compounds at Households in Ulaanbaatar City - Galsuren, Jargalsaikhan; Dambadarjaa, Davaalkham; Boldbaatar, Buyantushig; Erdenechimeg, Zoljargal; Gombojav, Enkhjargal (Central Asian Journal of Medical Sciences, 2023)
Objectives: VOCs, or Volatile Organic Compounds, are a group of organic chemicals that can easily evaporate into the air at room temperature. They are called “volatile” because they have high vapor pressure and can readily form vapors or gases at normal atmospheric conditions. To address this knowledge gap, we aimed to assess VOC exposure and its associated health risks. Method: Samples were collected through the adsorbent tube, followed by detachment from the solvent by organic solvents solvent or methanol, and analyzed by gas chromatographic equipment attached with a flame ionization detector (FID). We selected 150 households from the Chingeltei and Bayangol districts in Ulaanbaatar city, specifically sections 4, 5, 6, and 12, to examine the levels of indoor VOCs in this study. We used the nonparametric Mann-Whitney U test to compare medians of VOC levels for two independent groups. Kruskal-Wallis test was carried out to determine if there was any significant difference between medians of VOC levels for more than two independent groups, including the type of paint used, wooden furniture used, and construction year. Results: We found no significant difference in benzene concentration among different types of households (p<0.8112). The highest benzene concentration (0.181 µg/m3) was measured in apartments and houses. Although there was no statistically significant difference between household room types, the kitchen had a higher benzene concentration than other rooms (p<0.8156). Factors such as household total volume, building construction year, and materials used for floors and walls did not significantly affect indoor benzene concentration. Most of the day, the benzene levels exceeded the standards set by the Indoor Air Quality Act of South Korea and the recommended levels by the Health Minister and Construction and Urban Development Minister of Mongolia. In 133 households in Ulaanbaatar city, indoor VOCs, specifically benzene concentration, exceeded the recommended level stated in Order No. A105/08 by the Health Minister and Construction and Urban Development Minister in 2017. Conclusion: Indoor benzene concentration did not vary significantly based on household type, room type, household volume, building construction year, construction wall material, construction floor material, whether new furniture was purchased or the dwelling was repaired and painted within the last two months, proximity to major roads, or indoor smoking status.